Des principes Gaulliens de politique etrangere aux realites transregionales de l’apres-guerre froide (International relations and international law Journal, 2018)
This article is dedicated to study one of the aspects of Charles deGaulle`s legacy, the first President of the Fifth Republic in France, namelyto his principles in foreign policy. How relevant are these principles today,in the conditions of the post cold war international relations? Key in conceptof French diplomacy are terms of national independence. Whole Generalde Gaulle`s activity in period of exile, and in the period of presidency wasdevoted to general aim – to achieve true national independence of Francein the international level. Official position and the concept of Gaullismin the issue of European integration was also subordinated to the task topreserve the independence of member states of the European Community.On the other hand, namely Charles de Gaulle advocated the principles ofmultilateralism. Despite the change of geopolitical situation after the endof the cold war, France retains basic principles of its own foreign policyfounded by S. de Gaulle. The essence of these principles – preservationof national independence of France in the name of its national interests.Key words: Gaullism, French foreign policy, interregional cooperation,multilateralism, national interests.